Well-Being Elective in Health Professional Education: A Pilot Study - Desirée N. Shapiro; Nikki Ashtiani; Raphael Cuomo; Candis M. Morello (Pharmacy, 2026)
Background: Health professional training is inherently challenging, with elevated rates of burnout, stress, and diminished well-being. Dedicating curricular time to well-being education may build awareness and skills to help students navigate these demands. Methods: A 10-week well-being elective was designed and implemented for health professional students. Participants in the intervention group were predominantly pharmacy students. This pilot feasibility study used a pre- and post-intervention survey design with a comparison group. Course evaluation, self-reported confidence, knowledge, skills, and attitudes about well-being practices, and measures of empathy, compassion, stress, social support, and burnout were assessed [n = 29 intervention, n = 24 comparison]. Results: Students in the elective reported high satisfaction in the course and significantly greater improvements than those in the comparison group in confidence applying wellness strategies in their personal and academic lives, identifying mental health and wellness resources, preparing nourishing meals, showing up authentically, using mindfulness, practicing self-compassion, as well as in frequency of reflecting on wellness, practicing mindfulness and self-compassion, and applying wellness strategies (all p < 0.05). Prioritization of wellness and feelings of social connection also improved significantly more than in the comparison group. At 6-week delayed follow-up, participants reported significantly greater increases in confidence in preparing nourishing meals, showing up authentically, applying mindfulness, as well as in frequency of mindfulness practice, reflection on wellness, and greater gains in social connection (all p < 0.05). No significant between-group differences were observed on the validated measures of empathy, burnout, or self-compassion. Conclusions: A novel well-being elective designed for health professional students significantly improved select well-being-promoting behaviors and emotional connectedness among participating students. Scalable curricula may bolster student well-being and foster community in demanding academic environments.